Role of oxidative stress in opiate withdrawal and dependence: Exploring the potential use of honey - Nor Hidayah Abu Bakar, Siti Norhajah Hashim, Nasir Mohamad, Rohayah Husain, Liyana Hazwani Mohd Adnan, Halim Shariff, Nur Husna Zakaria (Journal of Applied Pharmaceutical Science, 2015)
Opiate dependence and withdrawal is a worldwide public health problem and give a significant burden to society. In exploring the problems of opiate dependence and withdrawal, oxidative stress in thought to be involved in the mechanism of the development of dependence and tolerance to morphine. Therefore, there is possibility that antioxidant has the role to reduce the oxidative stress leading to opiate dependence and withdrawal. In this mini review we describe the evidence of relationship between oxidative stress and opiate dependence. We also describe the evidence of honey which has been claimed to have high antioxidant properties and its promising potential to reduce oxidative stress in opiates dependence and tolerance individuals.
Keywords: Opiate dependence and withdrawal, antioxidant, oxidative stress, honey.